Normal Development of the Perineuronal Net in Humans; In Patients with and without Epilepsy. (1st August 2018) - Rogers, Stephanie L.; Rankin-Gee, Elyse; Risbud, Rashmi M.; Porter, Brenda E.; Marsh, Eric D.
Highlights: This is the first presentation of the human developmental timeline of the perineuronal net. The perineuronal net begins to form in the second month of life and reaches its mature appearance around 8 years of age. Perineuronal net development is not altered in a few patients with intractable epilepsy. Abstract: The perineuronal net (PN), a highly organized extracellular matrix structure, is believed to play an important role in synaptic function, including maturation and stabilization. In addition to its role in restricting plasticity, alterations in the PN are implicated in disorders such as epilepsy and schizophrenia. However, the time course of PN development is not known in humans. Therefore we set out to document the developmental timeline of the PN formation in humans in 14 frontal and hippocampal specimens from donors aged 27 days to 31 years old. Using immunohistochemistry and western blotting, we demonstrate that the PN begins to form as early as the second month of life but does not reach its robust, mature appearance until around 8 years of age, though aggrecan cleavage products are observed prior to this. A similar developmental time course was observed in specimens from epilepsy patients. Our data suggest that aggrecan is present early in development but the structured PN develops throughout early childhood, similar to what has been observed in rodents. This timeline provides information for future pathological studies on the role of the PN in disease and an additional parallel between human and rodent development.